An examination of a cycle of coping with strain among registered citizens' families. Issue 2 (3rd April 2017) - Bailey, Danielle J. S.; Sample, Lisa L.
Abstract: The consequences of sex offender laws for both registered sex offenders and their family members have been well documented. Rarely studied, however, are how sex offender families cope with these consequences over time, a problematic gap given the collateral stigmatization family members face by society and the important role they play in the desistance process for sex offenders. Using a strain perspective, the current research study used qualitative interviews with 38 sex offender family members to explore the type of coping strategies used by sex offender family members and the dynamic evolution of these strategies over time. Our findings provide practical implications for aiding registered sex offenders and their families in an effort to increase public safety.